Have Girls Been Left behind during the COVID-19 Pandemic? Gender Differences in Pandemic Effects on Children's Mental Wellbeing - Silvia Mendolia; Agne Suziedelyte; Anna Zhu (Institute of Labor Economics (IZA), 2021)
Using data from the UK, we show that girls have been affected more than boys by the COVID-19 pandemic in terms of their mental wellbeing. These gender differences are more pronounced in lower-income families. Our results are consistent with previous findings of larger pandemic effects on mental health of women.
Keywords: I10; I31; J13; 330; COVID-19; pandemic; mental health; children